2023
DOI: 10.1039/d3ta00978e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and ionic effects of sulphur and other acidic adsorbates on the surface of an SOFC cathode material

Abstract: A combined experimental and computational approach reveals electronic and ionic effects of acidic adsorbates on mixed conducting oxide surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 83 publications
2
8
0
Order By: Relevance
“…Upon exposure of pristine surfaces to considerable gas phase pressures (> 10 −3 mbar), a new oxygen species appears at 532 eV, alongside a weak corresponding S species 19 . Consistent with earlier studies, where SO 2− 4 adsorbates induced a significant increase in the work function of LSC 13 , this phenomenon could be reproduced for PCO, albeit with a less pronounced increase. This is in line with the quantification of SO 2− 4 adsorbates from XPS data, revealing higher concentrations on LSC surfaces (55 % coverage on LSC vs. 25 % coverage on PCO), indicating the strong affinity of the basic LSC surface for acidic adsorbates.…”
Section: Tuning the Work Function With Ultra-thin Oxide Layerssupporting
confidence: 91%
See 2 more Smart Citations
“…Upon exposure of pristine surfaces to considerable gas phase pressures (> 10 −3 mbar), a new oxygen species appears at 532 eV, alongside a weak corresponding S species 19 . Consistent with earlier studies, where SO 2− 4 adsorbates induced a significant increase in the work function of LSC 13 , this phenomenon could be reproduced for PCO, albeit with a less pronounced increase. This is in line with the quantification of SO 2− 4 adsorbates from XPS data, revealing higher concentrations on LSC surfaces (55 % coverage on LSC vs. 25 % coverage on PCO), indicating the strong affinity of the basic LSC surface for acidic adsorbates.…”
Section: Tuning the Work Function With Ultra-thin Oxide Layerssupporting
confidence: 91%
“…While previous studies have used the Smith acidity of the decoration as a descriptor to predict these changes 9,13,14 , we introduce the ionic potential of surface cations as an alternative metric to describe surface acidity. Based on the definition by Cartledge 15 , we define the surface ionic potential φ as the ratio of ionic charge q and ionic radius r, averaged over the surface cation stoichiometry (with cation fractions x i )…”
Section: Tuning the Work Function With Ultra-thin Oxide Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the evolution of charge carrier concentrations in such heterointerfaces is highly nontrivial and requires further computational investigation, going beyond the scope of this study. At this point, we also want to refer to a recent study on the effects of acidic adsorbates on LSC surfaces, combining experimental and computational approaches . Similar to acidic decorations, acidic adsorbates cause a significantly increased surface exchange resistance as well as an increased work function (negative surface charge) and charge redistribution in this system has largely been associated with oxygen atoms and charge transfer toward the adsorbate.…”
Section: Mechanistic Discussionmentioning
confidence: 99%
“…As a last noteworthy aspect, we suspect that surface decorations also influence reaction energetics such as adsorption equilibria, 49 further complicating the situation. This claim is again supported by recent computational results on acidic adsorbates on LSC, 51 where calculations revealed that acidic adsorbates cause strongly increased adsorption barriers for O 2 molecules and render O 2 adsorbates in surface vacancies energetically unfavorable.…”
Section: ■ Mechanistic Discussionmentioning
confidence: 99%